fx = exsinx, then f6x = ? from Mat

Previous Year Papers

Download Solved Question Papers Free for Offline Practice and view Solutions Online.

Test Series

Take Zigya Full and Sectional Test Series. Time it out for real assessment and get your results instantly.

Test Yourself

Practice and master your preparation for a specific topic or chapter. Check you scores at the end of the test.
Advertisement

 Multiple Choice QuestionsMultiple Choice Questions

1021.

If y = sin-1 x,  then 1 - x2dy2dx2 is equal to

  • - x dydx

  • 0

  • xdydx

  • xdydx2


1022.

If f : R  R is defined byf(x) = x - 2x2 - 3x + 2  if x  R - 1, 2                      2           if x = 1                      1           if x = 2 thenlimx2 fx - f2x - 2 = 

  • 0

  • - 1

  • 1

  • 12


1023.

If f :R  R is defined byf(x) = x - 2x2 + 3x + 2  if x  R - - 1, - 2           - 1      if  x = - 2              0         if  x = - 1Then f is contineous on the set 

  • R

  • R - - 2

  • R - - 1

  • R - - 1, 2


1024.

If f : R  R is an even function which is twice differentiable on R and f''(π) = 1, then f''(- π) is equal to

  • - 1

  • 0

  • 1

  • 2


Advertisement
1025.

Observe the following statements

I. f(x) = ax41 +bx- 40  f''xfx = 1640x- 2

II. ddxtan-12x1 - x2 = 11 + x2

which of the following is correct ?

  • I is true, but II is false

  • Both I and II are true

  • Neither I nor II is true

  • I is false, but II is true


1026.

If f(x) = 10cosx + 13 + 2xsinx, then f''x + fx is equal to

  • cos(x)

  • 4cos(x)

  • sin(x)

  • 4sin(x)


1027.

If x1 + y + y1 +x= 0, then dydx is equal to

  • 11 +x2

  • - 11 +x2

  • 11 +x2

  • 11 -x2


1028.

If u = sin-1xy + tan-1yx, then the value of xux + yuy is

  • 0

  • 1

  • 2

  • None of these


Advertisement
1029.

If xy = yx, then xx - ylogxdydx is equal to :

  • yy - xlogy

  • yy + xlogy

  • xx + ylogx

  • xy - xlogy


Advertisement

1030.

fx = exsinx, then f6x = ?

  • e6xsin6x

  • - 8excosx

  • 8exsinx

  • 8excosx


B.

- 8excosx

       fx = exsinx f'x = excosx +sinxexf''x = excosx - exsinx +exsinx +  excosx             = 2 excosxNow, f'''x = - 2exsinx + 2excosxand     fivx = - 2exsinx - 2excosx + 2excosx - 2exsinx                   = - 4exsinx           fvx =  - 4excosx - 4exsinx          fvix = - 4excosx + 4exsinx + 4exsinx - 4excosx                  = - 8exsinx


Advertisement
Advertisement